2016
DOI: 10.1016/j.stemcr.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Xeno-Free and Defined Human Embryonic Stem Cell-Derived Retinal Pigment Epithelial Cells Functionally Integrate in a Large-Eyed Preclinical Model

Abstract: SummaryHuman embryonic stem cell (hESC)-derived retinal pigment epithelial (RPE) cells could replace lost tissue in geographic atrophy (GA) but efficacy has yet to be demonstrated in a large-eyed model. Also, production of hESC-RPE has not yet been achieved in a xeno-free and defined manner, which is critical for clinical compliance and reduced immunogenicity. Here we describe an effective differentiation methodology using human laminin-521 matrix with xeno-free and defined medium. Differentiated cells exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 25 publications
0
31
0
4
Order By: Relevance
“…An approach that is currently under substantial investigation is the replacement of dysfunctional, diseased RPE with cells derived in vitro from stem cell differentiation. Preclinical as well as early clinical reports suggest that this strategy is safe and allows the newly transplanted RPE to effectively perform functions such as phagocytosis, fluid and nutrient transport, and photoreceptor support, leading to potential restoration of vision . In addition, there are many features that make the eye an attractive organ for cell replacement and regenerative therapy approaches, such as the requirement of fewer cells for therapeutic intervention in comparison with other larger organs, accessibility and ease of monitoring, potential immune privilege, and presence of the retinal‐blood barrier, leading to separation from systemic circulation .…”
Section: Introductionmentioning
confidence: 99%
“…An approach that is currently under substantial investigation is the replacement of dysfunctional, diseased RPE with cells derived in vitro from stem cell differentiation. Preclinical as well as early clinical reports suggest that this strategy is safe and allows the newly transplanted RPE to effectively perform functions such as phagocytosis, fluid and nutrient transport, and photoreceptor support, leading to potential restoration of vision . In addition, there are many features that make the eye an attractive organ for cell replacement and regenerative therapy approaches, such as the requirement of fewer cells for therapeutic intervention in comparison with other larger organs, accessibility and ease of monitoring, potential immune privilege, and presence of the retinal‐blood barrier, leading to separation from systemic circulation .…”
Section: Introductionmentioning
confidence: 99%
“…In efforts to evolve from laminin rich mouse ECM (Matrigel and Geltrex), most groups have focused on human laminin and vitronectin. Multiple publications have shown the ability to use these for culture of ESCs , and for laminins, iPSC culture. For example, Synthemax (Corning), a synthetic peptide with vitronectin elements, is a GMP‐compatible product marketed for ESC culture and which has seen limited use in the generation of iPSCs .…”
Section: Discussionmentioning
confidence: 99%
“…Another recently released product for cell therapy grade use is recombinant human laminin (Laminin‐521, BioLamina). Specifically, Laminin 521 has been demonstrated to work as a plate coating for culture of both ESC and iPSC lines , as well as for differentiation of stem cells to other cell types .…”
Section: Discussionmentioning
confidence: 99%
“…These scaffolds can be made of materials that include collagen and poly(lactic-co-glycolic acid) (PLGA) and it has been demonstrated that a basal support membrane is critical to long-term RPE survival after implantation [56]. It will be of interest to determine the most efficient transplantation method as both single cell suspensions and membrane supports show efficacy [56,57]. …”
Section: Amd and Bruch’s Membrane Pathologymentioning
confidence: 99%